Evaluative Study of the Implementation of the Independent Curriculum in Physical Education Elementary School Level Using the CIPP Model - Mulyadi, Mulyadi; Hidayatullah, Muhammad Furqon; Syaifullah, Rony; Riyadi, Slamet (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to evaluate the use of the Independent Curriculum in Physical Education Learning at the elementary school level using the CIPP (Context, Input, Process, Product) model approach. This research uses a qualitative case study approach in 12 public elementary schools in Mojogedang District, Karanganyar Regency, Indonesia. Data was obtained through observation, semi-structured interviews, and document analysis. The significance of this research is Penjas learning at the elementary school level. The main focus of this research lies in the need to ensure the effectiveness of implementing the Merdeka Curriculum. As a result of this research, it was found that there were significant variations in the implementation of the Independent Curriculum between schools. Although the context aspect highlights the importance of developing students holistically, there are differences in the ideal concept and its implementation. Input evaluations show significant differences in school readiness, especially in teacher capabilities and resource availability. Product evaluation shows various differences in efforts to develop student competencies. The results of this research conclude that a more differentiated and contextual implementation strategy is needed, as well as getting sustainable support in teacher professional development and improving educational infrastructure.